2019
DOI: 10.1016/j.jsp.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A teacher-led vicarious contact intervention in culturally mixed classrooms with in- and outgroup role models of intergroup friendship

Abstract: Existing prejudice-reduction interventions in schools mainly target majority students and are mostly conducted by researchers, which limits their use for anti-discriminatory practices in culturally mixed schools. We tested a teacher-led intervention aiming at prejudice-reduction among both minority and majority adolescents through vicarious contact. The effects of indirect vicarious contact rest on observed ingroup role models of intergroup contact who have positive attitudes towards the outgroup, and vice ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
(76 reference statements)
0
12
0
2
Order By: Relevance
“…These findings are not only restricted to extended contact, as recent research has shown that perceived ingroup norms also account for the effect of alternative forms of indirect contact such as vicarious contact (e.g., Mäkinen et al, 2019;Vezzali et al, 2014). Finally, this effect appears even when controlling for direct intergroup contact (e.g., Gomez et al, 2011), and is independent of the effect of other mediators such as intergroup anxiety (e.g., Paolini et al, 2004) and inclusion of other in the self (e.g., Cameron & Rutland, 2006;see R. N. Turner et al, 2008).…”
Section: Social Normsmentioning
confidence: 74%
“…These findings are not only restricted to extended contact, as recent research has shown that perceived ingroup norms also account for the effect of alternative forms of indirect contact such as vicarious contact (e.g., Mäkinen et al, 2019;Vezzali et al, 2014). Finally, this effect appears even when controlling for direct intergroup contact (e.g., Gomez et al, 2011), and is independent of the effect of other mediators such as intergroup anxiety (e.g., Paolini et al, 2004) and inclusion of other in the self (e.g., Cameron & Rutland, 2006;see R. N. Turner et al, 2008).…”
Section: Social Normsmentioning
confidence: 74%
“…The social normative structure within which an intervention is realized may also dramatically change the impact of the intervention (Eller, Abrams, et al, 2017; for the role of structural transitions in determining intergroup relations, see also Birtel, Reimer, Wölfer, & Hewstone, 2020). In addition, the impact of who administers the intervention (e.g., researcher or teacher), as well as interactions between researchers and practitioners, are likely to have a deep impact on the effectiveness of the intervention (Cameron & Rutland, 2016;Cameron & Turner, 2017;Mäkinen et al, 2019). These factors are often considered unimportant and are not addressed or discussed meaningfully in social psychological research.…”
Section: Testing Contact Models With Naturalistic Interventionsmentioning
confidence: 99%
“…Vicarious contact can be defined as the observation of interactions between ingroup and outgroup members (Dovidio et al., 2011; Vezzali et al., 2014). When tested in the laboratory it has generally been operationalized as video watching (Mazziotta et al., 2011; Preuß & Steffens, 2020) and in naturalistic contexts as story reading; that is, short ad hoc created stories where ingroup characters have positive interactions with outgroup characters (Cameron & Rutland, 2006; Mäkinen et al., 2019; McKeown et al., 2017; but see Vezzali et al., 2019). There is now a large body of evidence showing that observing positive intergroup interactions is associated with reduced prejudice (Mazziotta et al., 2011; West & Turner, 2014).…”
Section: Media Vicarious Contactmentioning
confidence: 99%